Collected Stories of Marvellous and Miraculous Events : A 16th Century Malay Cosmogony - Riddell, Peter, (Asian Studies E-Books Online, Collection 2026., 2026)
This book presents for the first time the oldest surviving example of universal history to be produced in the Malay-Indonesian World. In the process it challenges previous scholarly assumptions about pioneering works in this genre. The study is based on a document contained in Cambridge University Library manuscript Or Gg.6.40 dating from the turn of the 17th century. The initial chapters in this book situate the manuscript within its historical, social and religious context in the Sultanate of Aceh. This is followed by a transliteration of the Jawi text and translation into English, as well as the original Jawi text of the work.